1996
DOI: 10.1159/000111431
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Compartmentation of Glutamate and Glutamine in Cultured Rat Brain Astrocytes

Abstract: Studies from several groups have provided evidence that glutamate and glutamine are metabolized in different compartments in astrocytes. In the present study we measured the rates of 14C02 production from U-[14C]glutamate and U-[14C]glutamine, and utilized both substrate competition experiments and the transaminase inhibitor aminooxyacetic acid (AOAA) to obtain more information about the compartmentation of these substrates in cultured rat brain astrocytes. The rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 19 publications
5
84
0
Order By: Relevance
“…These observations are consistent with existing evidence that GDH in brain functions mainly toward the oxidative deamination of glutamate (31). On the other hand, there is little evidence that GDH is involved in the synthesis of glutamate in brain, as the enzyme has a high K m for ammonia (10 -20 mM) and the NAD ϩ /NADH ratio is high in this organ (31). However, local increases in ammonia concentration could facilitate the reductive amination of ␣-ketoglutarate, as has been suggested for the "glutamate/glutaminebranched chain amino acid shuttle" that is thought to be involved in the cycling of ammonia between neurons and astro-FIGURE 7.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These observations are consistent with existing evidence that GDH in brain functions mainly toward the oxidative deamination of glutamate (31). On the other hand, there is little evidence that GDH is involved in the synthesis of glutamate in brain, as the enzyme has a high K m for ammonia (10 -20 mM) and the NAD ϩ /NADH ratio is high in this organ (31). However, local increases in ammonia concentration could facilitate the reductive amination of ␣-ketoglutarate, as has been suggested for the "glutamate/glutaminebranched chain amino acid shuttle" that is thought to be involved in the cycling of ammonia between neurons and astro-FIGURE 7.…”
Section: Discussionsupporting
confidence: 93%
“…This requires conversion of glutamate to ␣-ketoglutarate catalyzed partly by GDH. These observations are consistent with existing evidence that GDH in brain functions mainly toward the oxidative deamination of glutamate (31). On the other hand, there is little evidence that GDH is involved in the synthesis of glutamate in brain, as the enzyme has a high K m for ammonia (10 -20 mM) and the NAD ϩ /NADH ratio is high in this organ (31).…”
Section: Discussionsupporting
confidence: 89%
“…Subsequently, glutamate is converted into glutamine by astrocytic glutamine synthetase and secreted into the extracellular fluid, from which it is taken up by neurons for conversion into glutamate, aspartate and γ-aminobutyric acid [36,38,39]. Oxaloacetate, produced by PC, can also participate in this glutamate\glutamine cycle [40], and a recent study has shown that PC can alter the rate of de no o astrocytic synthesis of glutamate by increasing the amount of tricarboxylic acid cycle intermediates [39].…”
Section: Role Of Pc In Astrocytesmentioning
confidence: 99%
“…These are the excitatory amino acid transporters 1 and 2 (EAAT1 and EAAT2 in humans, the rat counterparts being GLAST and GLT-1, respectively) (6,29). Glutamate taken up by astrocytes is converted to glutamine by glutamine synthetase (GS; EC 6.3.1.2), and also passes into the astrocytic tricarboxylic (TCA) cycle (39) by conversion into ␣-ketoglutarate by glutamate dehydrogenase (GDH; EC.1.4.1.3). If glutamate management is impaired within astrocytes, this will compromise the functional integrity of the CNS in general and that of neurons and oligodendrocytes in particular, as these cells de-pend on metabolic precursors provided by astrocytes (48) and are highly sensitive to excessive concentrations of extracellular glutamate (7,37,54).…”
mentioning
confidence: 99%